2012
DOI: 10.1590/s0104-42302012000600009
|View full text |Cite
|
Sign up to set email alerts
|

Maus-tratos contra a criança e o adolescente no Estado de São Paulo, 2009

Abstract: Public policies should guarantee that children and adolescents have a healthy and violence-free life. The analysis of the notifications is an important tool to establish prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
2
8
1
3
Order By: Relevance
“…Sexual violence was the most frequently notified type among children and adolescents in Manaus during the study period. This result diverges from the majority of studies conducted in Brazil's different regions, [11][12][13][14][15][16][17][18][19][20][21][22] which are conclusive as to negligence and physical violence being the most notified types of violence in childhood. Notwithstanding, a study conducted in Belém, capital of the state of o Pará, also found that sexual violence was the most frequently notified type (41.8%) among violence practiced against young people.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Sexual violence was the most frequently notified type among children and adolescents in Manaus during the study period. This result diverges from the majority of studies conducted in Brazil's different regions, [11][12][13][14][15][16][17][18][19][20][21][22] which are conclusive as to negligence and physical violence being the most notified types of violence in childhood. Notwithstanding, a study conducted in Belém, capital of the state of o Pará, also found that sexual violence was the most frequently notified type (41.8%) among violence practiced against young people.…”
Section: Discussioncontrasting
confidence: 92%
“…11,19,23 As indicated by other studies on this subject in Brazil, frequent use of physical force in these incidents may be related to abuse of power, authority, imposing limits and to the condition of being subordinated. [11][12][13][14]16,17,[20][21][22] With regard to the perpetrators' characteristics and kinship with children, the results presented in this study are similar to those of other research, by revealing, for example, that the main perpetrator was a family member. 11,[13][14][15]17,18 In the case of adolescents, however, friends or acquaintances of the victim were the main perpetrators of violence.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Estudo espanhol (17) com crianças vítimas de abuso sexual relatou que 62% dos agressores também se encontravam no ambiente familiar. Em comparação a outros estudos brasileiros (4,8,(10)(11)(13)(14)18) , houve unanimidade sobre o local de ocorrência desses atos. O lar é cenário dos diversos tipos de violência, o que descontrói na criança e no adolescente a imagem de lugar protetor e de confiança.…”
Section: Introductionunclassified
“…A privacidade do domicílio cria um ambiente sem testemunhas para a violência sexual, muitas vezes velada pela própria família, gerando um isolamento social e dificultando a adoção de medidas interventivas (8,11) . A violência sexual está muito presente na família brasileira, encontrando-se no núcleo familiar os principais responsáveis por esses atos (18) .…”
Section: Introductionunclassified